Trading European sovereign bonds: the microstructure of the MTS trading platforms - Yiu Chung Cheung; Frank de Jong; Barbara Rindi (European Central Bank (ECB), 2005)
We study the microstructure of the MTS Global Market bond trading system, which is the largest interdealer trading system for Eurozone government bonds. Using a unique new dataset we find that quoted and effective spreads are related to maturity and trading intensity. Securities can be traded on a domestic and EuroMTS platform. We show that despite the apparent fragmentation of trading, both platforms are closely connected in terms of liquidity. We also study the intraday price order flow relation in the Euro bond market. We estimate the price impact of order flow and control for the intraday trading intensity and the announcement of macroeconomic news. The regression results show a larger impact of order flows during announcement days and a higher price impact of trading after a longer period of inactivity. We relate these findings to interdealer trading and to the structure of European bond markets.
Keywords: F31; C32; 330; Bonds markets; Microstructure; order flow; Eurobond; Marktmikrostruktur; EU-Staaten